Plasma contains ultrashort single-stranded DNA in addition to nucleosomal cell-free DNA - Jordan Cheng; Marco Morselli; Wei-Lun Huang; You Jeong Heo; Thalyta Pinheiro-Ferreira; Feng Li; Fang Wei; David Chia; Yong Kim; Hua-Jun He; Kenneth D. Cole; Wu-Chou Su; et al. (iScience, 2022)
Summary: Plasma cell-free DNA is being widely explored as a biomarker for clinical screening. Currently, methods are optimized for the extraction and detection of double-stranded mononucleosomal cell-free DNA of ∼160bp in length. We introduce uscfDNA-seq, a single-stranded cell-free DNA next-generation sequencing pipeline, which bypasses previous limitations to reveal a population of ultrashort single-stranded cell-free DNA in human plasma. This species has a modal size of 50nt and is distinctly separate from mononucleosomal cell-free DNA. Treatment with single-stranded and double-stranded specific nucleases suggests that ultrashort cell-free DNA is primarily single-stranded. It is distributed evenly across chromosomes and has a similar distribution profile over functional elements as the genome, albeit with an enrichment over promoters, exons, and introns, which may be suggestive of a terminal state of genome degradation. The examination of this cfDNA species could reveal new features of cell death pathways or it can be used for cell-free DNA biomarker discovery.